Temperature Effects on Tall Steel Framed Buildings Part 2-Structural Analysis - West, Harry H.; Kar, Anil K. (Engineering Journal, 1970)
Recent trends in architectural design have led to the construction of multistory structures with the exterior columns partially or fully exposed. Such an arrangement provides a pleasing aesthetic effect with strong vertical lines. However, this arrangement subjects the exposed columns to severe temperature variations, whereas the interior columns remain in a controlled environment. These variations induce changes of length of the exterior columns which induce forces throughout the structure. The magnitude of these forces depends on many things, but of primary importance is the height of the structure. For low structures, the effects are small; however, for tall buildings they may be significant. The response of structural members to temperature variations is well known, but little work has been done on the analysis and design of tall steel buildings in which temperature changes occur in the exposed columns. Khan and Fintel developed a procedure for the analysis of temperature effects in reinforced concrete structures. Their procedure is an approximate iteration process which assumes rigid beam-to- column connections. This assumption is valid for reinforced concrete structures; however, steel structures may have rigid or semi-rigid connections. There are several schemes of complete structural analysis available to the designer that can be used for the temperature problem. The Structural Design Language (STRUDL) of Integrated Civil Engineering System (ICES) is an example of such a scheme. This problem-oriented program provides a stiffness method of analysis for the complete frame. However, at present, semi-rigid joints and complicated temperature gradients cannot be handled. STRUDL is used for comparison in this study; however, the cost prohibits its use for the parameter study.